Detekcija kravljeg imunoglobulina G (lgG) kao parametra patvorenja kozjeg i ovčjeg mlijeka i mliječnih proizvoda - Smajlović, Ahmed, veterinar (Array, 2021)
The most common method of milk adulteration is the addition of undeclared types of milk, such as cow"s milk (due to its lower cost) to sheep and goat milk and milk products. In order to avoid the undeclared addition of cow"s milk and improve consumer protection, it is common practice to check the authenticity of a product by examining its contents. For the purposes of this study, the ELISA method was applied and tested to detect cow immunoglobulin G (IgG) in mixtures of various types of milk under experimental conditions. Following this, we aimed to determine the current situation on the BiH market in terms of content of undeclared milk types, by detecting the presence of cow immunoglobulin G (IgG) as a parameter of adulteration in samples of sheep and goat milk and milk products. We established that cow"s milk was present in almost half of the tested samples of goat and sheep milk and their products, while the highest number of positive samples of the presence of cow"s milk was found in sheep milk products.